2020
DOI: 10.1177/0300060520926075
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block combined with local infiltration analgesia versus isolated adductor canal block in reducing pain and opioid consumption after total knee arthroplasty: a systematic review and meta-analysis

Abstract: Objective To evaluate the efficacy and safety of the addition of local infiltration analgesia (LIA) to adductor canal block (ACB) for pain control after primary total knee arthroplasty (TKA). Methods Two reviewers independently searched for potentially relevant published studies using electronic databases, including PubMed® (1966 to June 2019), Embase® (1974 to June 2019) and Web of Science (1990 to June 2019). The results were pooled using the random-effects model to produce standard mean differences for cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A total of 26 systematic reviews and meta-analyses were identified reporting ACB in TKA [ACB versus FNB (n U 8), [111][112][113][114][115][116][117][118] ACB versus LIA (n ¼ 10), [138][139][140][141][142][143][144][145][146][147] and ACB technique (n ¼ 7)]. [148][149][150][151][152] Five RCTs compared ACB with saline ACB (either bolus or repeated boluses or continuous infusion) (Table S1, http://links.lww.com/ EJA/A701).…”
Section: Adductor Canal Blockmentioning
confidence: 99%
“…A total of 26 systematic reviews and meta-analyses were identified reporting ACB in TKA [ACB versus FNB (n U 8), [111][112][113][114][115][116][117][118] ACB versus LIA (n ¼ 10), [138][139][140][141][142][143][144][145][146][147] and ACB technique (n ¼ 7)]. [148][149][150][151][152] Five RCTs compared ACB with saline ACB (either bolus or repeated boluses or continuous infusion) (Table S1, http://links.lww.com/ EJA/A701).…”
Section: Adductor Canal Blockmentioning
confidence: 99%
“…Consistent with previous studies, we also failed to show that the addition of an iPACK block improves functional outcomes or quality of recovery after total knee arthroplasty, irrespective of pain score differences in the first 24 h. 13 Both the study and control groups in the current study received a single IV dexamethasone dose, single-shot adductor canal block, intrathecal morphine (100 μg), and periarticular local anesthesia infiltration for postoperative analgesia (table 1). The synergistic analgesic effect of combining periarticular local anesthesia infiltration and single-dose adductor canal block can significantly delay rescue analgesia, 26 reduce cumulative opioid requirements, 27 and improve range of motion 28 and early discharge after total knee arthroplasty. 29 The addition of intrathecal morphine to adductor canal block and periarticular local anesthesia infiltration can further improve analgesia and reduce postoperative opioid requirements.…”
Section: Multimodal Analgesia For Knee Arthroplastymentioning
confidence: 99%
“…It has become clear that periarticular LIA has better pain control with less opioid consumption than ACB alone [1,2]. Although the duration of single-dose LIA may not be long enough to cover the perioperative period, it has been shown that combining ACB with LIA can signi cantly reduce pain scores and morphine consumption compared with LIA alone [3][4][5]. However, this raises concerns about the potential risk of local anesthetic systemic toxicity (LAST), especially with the large doses of local anesthetic used in both LIA and ACB.…”
Section: Introductionmentioning
confidence: 99%